Between prayers and drums. Approaching two musical practices of the Peruvian Amazon - Irrazabal Laos, Korina Grelly (2018)
The present text unites two musical expressions located in different Amazonian communities: the ícaro of the Shipibo community, corresponding to a ritualized, non-open practice, and the movido típico of the locale of Pucallpa, corresponding to festive contexts and open or collective practice. Each one of these musics is addressed in a subsection by one author, following both the same methodological approach. The musicological focus is based on ethnography of the social context of the music, developed through written and multimedia data. This is followed by an analysis of the most significant musical characteristics including vocal and melodic transmission in the case of the ícaro, and rhythmic instrumentation in the case of the traditional movido, theorizations that are expressed in musical transcription proposing special forms of sonic representation along with conventional music notation. The following section addresses aspects of musical performance, as these aspects highlight the articulation that exists between the musician, the audience of the music, the social space, and the aesthetic and symbolic content itself of these musics. It addresses among other aspects the clothing, corporality, musical gesture, action of the instrument, and social interaction. Finally, considerations in the form of a preliminary conclusion are proposed in each case. Among these are emphasized the following, that the musical diversity of the Peruvian Amazon is multiple not only in forms of musical expression at an aesthetic level, but also it is multiple in social functions and in sustaining spaces of human life.